Taxonomic notes on Chinese Cercyon: description of a new species, new synonyms, and additional faunistic records (Coleoptera: Hydrophilidae: Sphaeridiinae) - Jia, Feng-Long; Fikáček, Martin; Ryndevich, Sergey K. (Zootaxa, 2011)
A new species, Cercyon (Clinocercyon) hanseni sp. nov., is described from Jiangxi and Guizhou Provinces, China. Based on a study of type material, the following synonymies are proposed for the species occurring in China: Cercyon signifer Hebauer, 2002 is synonymized with C. (s. str.) berlovi Shatrovskiy, 1999, Cercyon guangxiensis Wu et Pu, 1995 with Cercyon (s. str.) quisquilius (Linnaeus, 1761), Cercyon nigrostriatus Wu et Pu, 1995 with Cercyon (Clinocercyon) lineolatus (Motschulsky, 1863), Cercyon vicinaloides dʼOrchymont, 1925, and Cercyon tropisternus Wu et Pu, 1995 with Cercyon (Paracycreon) laminatus Sharp, 1873, and Cercyon linearis Wu et Pu, 1995 with Cercyon (Paracycreon) subsolanus Balfour-Browne, 1939. A lectotype is designated for Cercyon vicinalis var. vicinaloides dʼOrchymont, 1925. Three Palaearctic species are recorded from China for the first time: Cercyon (s. str.) ovillus Motschulsky, 1860, Cercyon (s. str.) olibrus Sharp, 1874 and Cercyon (s. str.) unipunctatus (Linnaeus, 1758). Additional faunistic data from China are provided for Cercyon berlovi and Cercyon nigriceps (Marsham, 1802). Cercyon amplelevatus Jia, 1995 is transferred to the genus Armostus Sharp, 1890. A checklist of all Cercyon species recorded from China is presented, along with a tentative identification key.